Políticas de fomento ao desenvolvimento de fármacos e medicamentos no Brasil: Panorama de 1998 a 2020 - Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The recent health crisis installed around the world because of the covid-19 pandemic has once again brought the debate on issues related to the development, production, and access to health technologies to the center of the government agenda. In Brazil, it exposed the national vulnerability due to its dependence on the importation of various technologies in this area, particularly drugs and medicines. Considering this situation, the objective of this text is to present an overview of the policies implemented from 1998 to 2020 to promote the development of drugs and medicines in Brazil, directly or indirectly, to identify aspects to be improved in the formulation of a new policy for that purpose. For that, the methodological framework of the executive evaluation of public policies was used. The justification for the implementation of policies and/or the purpose stated in their formal texts were used to capture the main problem addressed and the objective related to the pharmaceutical sector, which have been common to all of them. Results of studies on the pharmaceutical sector in Brazil were used to elaborate the explanation of the problem (problem tree) and the analysis of the policies implementation. Policies documents constituted the basic references for the identification of its specific objectives and for the elaboration of a logical model for the set of initiatives. Studies on policies available in the technical and scientific literature, as well as indicators defined considering the logical model developed, were used to analyze the intermediate and final results of government action. It was found that a series of measures were implemented to promote the development of drugs and medicines in the country in the analyzed period, but that the results of these measures to reduce the Brazilian dependence on the importation of these products were limited. Three main factors were identified as possible determinants of this situation: i) the little innovative profile of Brazilian companies; ii) the emergence of new products of biotechnological origin of high added value, and the increase in their importance in therapeutics; and iii) insufficient State action to leverage significant structural change in the pharmaceutical sector due to the fragmentation of initiatives and discontinuities in the governmental effort. Finally, it is recommended to formulate a new policy, focusing on the pharmaceutical sector, resulting from a medium and long-term state planning, aiming at the implementation of actions and the resources allocation sustained over time, and that considers the particularities and requirements of this sector in the fields of industrial and foreign trade policy, science, technology and innovation policy, and health policy.
Keywords: H59; H81; 330; drug development; drug industry; public policy; federal government; National Science; Technology and Innovation Policy; Unified Health System